2020
DOI: 10.1093/glycob/cwaa110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ST6GAL1 sialyltransferase expression in cancer cells

Abstract: The ST6GAL1 sialyltransferase, which adds α2–6 linked sialic acids to N-glycosylated proteins, is overexpressed in a wide range of human malignancies. Recent studies have established the importance of ST6GAL1 in promoting tumor cell behaviors such as invasion, resistance to cell stress and chemoresistance. Furthermore, ST6GAL1 activity has been implicated in imparting cancer stem cell characteristics. However, despite the burgeoning interest in the role of ST6GAL1 in the phenotypic features of tumor cells, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 130 publications
4
57
0
2
Order By: Relevance
“…N-acetylglucosaminyltransferases (MGAT1) regulated the tumour growth and invasion [25][26][27]. In addition, the sialyltransferase ST6GAL1 regulated the abnormal glycosylation of some tumour suppressor genes to promote tumourigenesis [28,29], suggesting that COG complex acts as upstream regulators of these genes to regulate their function in tumours. Moreover, glycosylation and trafficking defects in fibroblasts isolated from COG-deficient human patients have been found through several experimental approaches, suggesting that COG complex plays a key role in tumour metastasis by regulating protein glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylglucosaminyltransferases (MGAT1) regulated the tumour growth and invasion [25][26][27]. In addition, the sialyltransferase ST6GAL1 regulated the abnormal glycosylation of some tumour suppressor genes to promote tumourigenesis [28,29], suggesting that COG complex acts as upstream regulators of these genes to regulate their function in tumours. Moreover, glycosylation and trafficking defects in fibroblasts isolated from COG-deficient human patients have been found through several experimental approaches, suggesting that COG complex plays a key role in tumour metastasis by regulating protein glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the role of ST6GALI in the malignant phenotype (growth, survival, angiogenesis, apoptosis, invasion, resistance to cell stress, chemoresistance). Increased ST6GAL1 activity is determined by genetic instability and epigenetic, transcriptional, and posttranslational factors [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of sialic acids is modulated by sialyltransferases, a group of glycosyltransferases divided into four families: β-galactoside α2,3-sialyltransferases (ST3Gal-I-VI), β-galactoside α2,6-sialyltransferases (ST6Gal-I and -II), GalNAc α2,6-sialyltransferases (ST6GalNAc-I-VI), and α2,8-sialyltransferases (ST8Sia-I-VI) [ 28 ]. During cell differentiation and neoplastic transformation, the expression of sialyltransferases undergoes substantial alterations resulting in phenotypic changes [ 27 , 28 , 29 , 30 ]. Sialyltransferases are well known as crucial modulators of several important processes such as cell-cell communication, cell-matrix interaction, cell adhesion, cell signaling, and trafficking [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylated Akt also fosters S6 phosphorylation by mTORC1 leading to augmented protein synthesis, which triggers stemness through stimulated transcription (44). Expression of ST6 beta-galactoside alpha-2,6-sialyltransferase 1(ST6GAL1), which adds alpha2-6 lined sialic acid to glycosylated protein, is also upregulated in cancer malignancies specially in CSCs (79,80). ST6GAL1 expression corelated with other CSC markers in colorectal carcinoma (38,39) Renewal, cell proliferation and differentiation (27,40) samples from patient and induced chemoresistance (81).…”
Section: Glycosylation Of Signaling Pathwaysmentioning
confidence: 99%